Targeted α Therapies for the Treatment of Bone Metastases - Zustovich, Fable (Int J Mol Sci, 2017)
The skeleton is the target tissue for many types of tumors, and, recently, the survival of patients with prostate cancer metastasis has been increased using α-emitting drugs known as targeted α therapies. The use of α-radiopharmaceuticals in medicine was hypothesized at the beginning of the nineteenth century after the observation that α-radionuclides were associated with high cell-killing energy and low tissue penetration in healthy tissues. In the prostate cancer (PC) scenario, current research suggests that this class of radiopharmaceuticals has limited toxicity, and that the mechanism of action does not overlap with pre-existing drugs, allowing us to extend therapeutic armaments and address medical oncology towards personalized and precision medicine. Ongoing studies may extend these benefits also to bone metastases deriving from other neoplasms. The aim of this review is to summarize the current research on targeted α therapies and try to identify the right patient to be treated in the right time in order to integrate in these medications in the every-day clinical practice.